ANALISIS KEPUASAN PELANGGAN PROVIDER SELULERTELKOMSEL - Rama Fathurachman (2022)
This research is a quantitative research that aims to determine and prove the effect of Telkomsel Cellular Provider Product Quality, Price and Promotion on Customer Satisfaction. This study used active students of UPN Veteran Jakarta as a sample. Determination of the number of samples using Ferdinand's theory so that the number of samples used is 75 respondents with the Non-Probability Sampling method with the type of Purposive Sampling. The data collection technique uses a questionnaire by utilizing the Google Form Platform. Partial Least Square (PLS) was used as a data analysis tool. The measurement model of this research is the Validity and Reliability Test. The structural model of this research is the R2 Test, Path Analysis Coefficient, and Statistical T Test. The result of this research is that product quality has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction, promotion has a significant effect on customer satisfaction.